2018
DOI: 10.1038/s41467-018-03651-9
|View full text |Cite
|
Sign up to set email alerts
|

Conformational switching within dynamic oligomers underpins toxic gain-of-function by diabetes-associated amyloid

Abstract: Peptide mediated gain-of-toxic function is central to pathology in Alzheimer’s, Parkinson’s and diabetes. In each system, self-assembly into oligomers is observed and can also result in poration of artificial membranes. Structural requirements for poration and the relationship of structure to cytotoxicity is unaddressed. Here we focus on islet amyloid polypeptide (IAPP) mediated loss-of-insulin secreting cells in patients with diabetes. Newly developed methods enable structure-function enquiry to focus on intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 33 publications
1
55
1
Order By: Relevance
“…ER stress induces changes towards a more reducing cellular environment, which triggers amylin aggregation [ 111 ]. A very recent publication brings new insight into IAPP conformational structure requirements for the formation of pores and the cytotoxic mechanisms in diabetes [ 112 ]. IAPP-induced toxicity eventually triggers autophagy as a response to protect against ER-related cellular damage [ 113 , 114 ].…”
Section: Er Stress Induces Ir and Diabetesmentioning
confidence: 99%
“…ER stress induces changes towards a more reducing cellular environment, which triggers amylin aggregation [ 111 ]. A very recent publication brings new insight into IAPP conformational structure requirements for the formation of pores and the cytotoxic mechanisms in diabetes [ 112 ]. IAPP-induced toxicity eventually triggers autophagy as a response to protect against ER-related cellular damage [ 113 , 114 ].…”
Section: Er Stress Induces Ir and Diabetesmentioning
confidence: 99%
“…Human amylin induces cell membrane permeabilization and perturbation, endoplasmic reticulum (ER) stress, mitochondrial damage, and β-cell death [ 84 , 85 , 86 , 87 , 88 ]. Furthermore, human amylin extracellularly added to INS-1β-cells at toxic concentrations crosses the plasma membrane and approximately 50% of amylin is localized in mitochondria and 5% or less is localized in the ER [ 89 ]. Human amylin forms oligomers that subsequently form fibrils followed by amyloid deposits [ 90 ].…”
Section: Cytotoxicity Of Amylinmentioning
confidence: 99%
“…Orcein-related small molecule, O4, is another chemical chaperone that induces the disaggregation of human amylin [ 119 ]. ADM-116, a pentaquinoline foldamer, can permeate the plasma membrane and prevent mitochondrial damage induced by amylin [ 89 ]. Furthermore, ADM-116 prevents the formation of amylin aggregates, thereby protecting pancreatic islet β-cells from the cytotoxic effects of amylin [ 120 ].…”
Section: Protection Of Pancreatic Islet β-Cells From Cytotoxicity mentioning
confidence: 99%
“…[3] Previous studies also reported that hIAPP forms toxic oligomers, which are alpha-helical. [4][5][6] Because of the cellular toxicity that associates with amyloid formation, it is important to develop small molecule compounds that inhibit/prevent amyloid aggregation and toxicity. [7] One of the frequently investigated amyloid inhibitors is epigallocatechin-gallate (EGCG; the major catechin present in green tea) ( Fig.S1B), a polyphenolic compound found in green tea extract.…”
Section: Introductionmentioning
confidence: 99%